The Right to Research and the New Ways of Disseminating Scientific Knowledge: "Open Access" - Jesús de Benito-Castanedo (Universidad Nacional, Costa Rica, 2015)
This article embodies an introduction to the "open access" movement and the main features and tools derived from it. In addition, it raises awareness about the importance of access to research and to scientific knowledge.